ROLE OF LUNG ULTRASOUND DURING WEANING IN PATIENT WITH MITRAL REGURGITATION POST ANGIOPLASTY - Hassan, Mujtaba; Ansari, Muhammad Imran; Abubaker, Jawed; Umair, Madiha; Baloch, Komal; Karim, Musa; Salahuddin, Nawal (Journal of Ayub Medical College Abbottabad, 2022)
Background: We hypothesize that a change in lung ultrasound score (LUS) can assist in the early diagnosis of weaning-induced respiratory failure (RF). The objective of this study was to determine the utility of LUS in weaning patients with mitral regurgitation (MR) from mechanical ventilation (MV). Methods: This prospective observational study included patients with acute coronary syndrome (ACS) who required invasive MV after angiography/angioplasty. Echocardiography was performed and MR was recorded. When the patient was considered ready for extubation, a spontaneous breathing trial (SBT) was performed and pre- and post-SBT LUS was calculated. Patients who successfully passed the SBT were extubated and followed up for 48 hours for the signs of RF and outcomes. Results: We enrolled 215 patients, out of which MR occurred in 51(23.7%) patients. On post-SBT lung ultrasound, patients with MR were more likely to have B2 lines compared to those without MR; 15.7% vs. 3.7%; p=0.002 and mean LUS was significantly higher for patients with MR as compared to patients without MR; 2.75±3.21 vs. 1.37± 2.02; p<0.001. Post-extubation RF and mean CCU stay were significantly higher in MR patients, 49.0% (25) vs. 32.3% (53); p=0.030 and 3.53±1.54 days vs. 2.41±1.1 days; p<0.001 respectively. However, re-intubation and coronary care unit (CCU) mortality rate were not significantly different between patients with and without MR; 7.8% (4/51) vs. 3.7% (6/164); p=0.215, and 5.9% (3/51) vs. 3% (5/164); p=0.35 respectively. Conclusions: Bedside LU is a convenient tool to detect changes in cardiopulmonary interactions during weaning for patients with MR post-ACS.